Evaluación de los Cambios Periodontales en las Personas Invidentes de Nacimiento de la Ciudad de Neiva Implementando un Manual Sobre el Cuidado Bucal en el Lenguaje Braille (2020)
The following document refers to a research project to develop and evaluate the effectiveness of a manual of oral hygiene techniques in Braille for people who are blind from birth; For the development of this research, nine objectives were established based on the preparation of the manual of oral hygiene techniques in Braille; conducting a survey with basic knowledge about oral hygiene; the assessment of the oral health status (periodontal status of a population group of the blind);Plaque index; the performance of basic periodontal therapy to the study population; the socialization of the manual in Braille system), where oral hygiene techniques can be clearly evidenced according to indications, use of dental floss and the use of rinsing, the practice of an oral status examination after 2 weeks and the comparison of the results obtained before and after the manual was socialized. The results showed that once the manual was designed and socialized, the subsequent examinations practiced on the study population evidenced improvements in dental quadrants such as healthier teeth, reduction of gingivitis, among others; in conclusion, it was established that the manual is a fundamental guide as a pedagogical inclusion strategy to improve the oral hygiene condition of this population.